T-REGULATORY CELLS IN RHEUMATOID ARTHRITIS - E. L. Nasonov; E. N. Aleksandrova; A. S. Avdeeva; Yu. P. Rubtsov (Научно-практическая ревматология)
Autoimmune (immunoinflammatory) rheumatic diseases are defined as clinical syndromes whose development is associated with the abnormal activation of T cells, B cells, and many other cells of the immune system, which gives rise to the progressive inflammation and destruction of the viscera. In spite of the high efficiency of combined therapy with biologic agents and standard disease-modifying antirheumatic drugs, primarily methotrexate, less than half of patients with rheumatoid arthritis (RA) could achieve a significant clinical effect and, very rarely, sustained remission. The combined influence of genetic and environmental factors may lead to loss of immunological tolerance, the basis for which is an imbalance between the effector and regulatory components of the immune system. To restore tolerance without chronic nonspecific immunosuppression observed in the use of majority of current anti-inflammatory drugs (including GEBAs) is regarded as the most important task of pharmacotherapy for RA. The aim of the review is to discuss firstly the role of the so-called T regulatory (Treg) cells as one of the critical components for the maintenance of tolerance and secondly promises for the pharmacotherapy of RA associated with the correction of the functional activity of Treg cells.